2022
DOI: 10.1039/d1ob02401a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 12β-methyl-18-nor-avicholic acid analogues as potential TGR5 agonists

Abstract: In the quest for new modulators of the Farnesoid-X (FXR) and Takeda G-protein-coupled (TGR5) receptors, bile acids are a popular candidate for drug development. Recently, bile acids endowed with a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…3) [47][48][49]. Following our initial work on the synthesis of 12β-methyl-18-nor-BAs, we also recently published results from an investigation into the applicability of 12β-methyl-18-nor-avicholic acids as potential TGR5 agonists [47,48]. Our research revealed the 23(R)-methylated 12β-methyl-18nor-chenodeoxycholic acid (16) and the 17-epi-bile acid 17 as weak TGR5 activators [48].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…3) [47][48][49]. Following our initial work on the synthesis of 12β-methyl-18-nor-BAs, we also recently published results from an investigation into the applicability of 12β-methyl-18-nor-avicholic acids as potential TGR5 agonists [47,48]. Our research revealed the 23(R)-methylated 12β-methyl-18nor-chenodeoxycholic acid (16) and the 17-epi-bile acid 17 as weak TGR5 activators [48].…”
Section: Introductionmentioning
confidence: 75%
“…44-1.33 (m, 3H), 1.33-1.20 (m, 3H), 1.20-1.12 (overlapping signals: m, 1H and 1.16, s, 3H), 1.04-0.92 (overlapping signals: m, 2H and 0.97, d, J = 6.6 Hz, 3H), 0.90 (d, J = 6.8 Hz, 3H), 0.80-0.67 (m, 2H); 13 C NMR (125 MHz, CDCl 3 ) δ 211. 92, 174.20, 70.94, 54.59, 52.50, 51.41, 48.04, 46.12 (2C), 45.12, 42.59, 37.79, 37.44, 37.00, 35.01, 34.94, 34.46, 34.16, 30.01, 29.87, 29.00, 24.22, 23.50, 23.07, 21.13, 19.75 Methyl 12β-methyl-3α,7-di(trimethylsilyloxy)-25-homo-18-nor-5β-cholan-6( 7)-en-25-oate (48). Applying the same procedure as for the synthesis of compound 30, a solution of 47 (1.14 g, 2.72 mmol) in dry tetrahydrofuran (8 mL) was introduced dropwise into a solution of lithium diisopropylamide (2 M in THF/heptane/ethyl-benzene; 9.20 mL, 18.4 mmol) and trimethylsilyl chloride (2.90 mL, 22.9 mmol) in dry tetrahydrofuran (15 mL) at − 78 • C. After being stirred for another 40 min at this temperature the reaction mixture was treated with triethylamine (0.57 mL, 4.09 mmol) to yield 1.39 g (91%) of 48 as a colorless oil.…”
Section: N-(6α-ethyl-3α7α-dihydroxy-12β-methyl-17-epi-18-nor-5βcholan...mentioning
confidence: 99%
See 2 more Smart Citations
“…As part of a program to develop new bile acids with targeted activities, we established a scalable route to the two novel alkenes 1 and 2 ( Figure 1 ) from cholic acid via a Nametkin-type rearrangement [ 16 , 17 ]. Of the various chemical manipulations afforded to olefins, we were particularly interested in applying those that result in the formation of new ring systems.…”
Section: Introductionmentioning
confidence: 99%